Becoming an Innovative Learning Environment The Making of a New Zealand Secondary School - Wright, Noeline (Springer Singapore, 2018)
This book examines how a new school, physically designed as a modern learning environment, has come into being in New Zealand, particularly in relation to how it offers a curriculum for future citizens. The book does so by examining various aspects of the school's development, highlighting specific features of this new school. The book considers how flexible curriculum and assessment options, together with the practices of self-managing schools, support the provision of a well-balanced, coherent and future-oriented learning programme. It also illustrates how the school is implementing its vision through its curriculum, pastoral care, and community partnerships, and copes with being different from how other schools understand and embody the New Zealand Curriculum as well as the NCEA qualifications system. Further, it maps school leaders', teachers' and foundation students' thinking and perspectives about what it's like to become a new school, within the context of an education system that continues to evolve as changes in the broader social, political, economic and technological context influence and impact both the education system as a whole and individual schools.